APLIKASI MESIN CHOPPER UNTUK OPTIMALISASI PENGOLAHAN PUPUK ORGANIK - Atmika, I.K.A.; Suriadi, I.G.A.K.; Putra Negara, D.N.K.; Astawa, I.P.A. (Buletin Udayana Mengabdi; Vol 24 No 1 (2025): Buletin Udayana MengabdiDO - 10.24843/BUM.2025.v24.i01.p10, 2024)
The potential of cow manure in the Sato Amerta Utama livestock group in Baluk Village has not been utilized optimally to be used as organic fertilizer. Lack of knowledge in Human Resources (HR) to manage this potential, as well as a lack of processing equipment are part of the problem. The solution offered is increasing the capacity of human resources to be able to manage Natural Resources (SDA) and provide leverage and create them to improve the welfare of Sato Amerta Utama Gapoktan members in particular, and the welfare of society more broadly. To achieve this target, collaboration is carried out with partners, namely Gapoktan Sato Amerta Utama. The method that will be used to overcome the problem of weak human resource capacity is through the application of several models, namely; Participation Assessment (PRA), Independent Capacity Building (ICB) model, and Technology Transfer (TT) model. The PRA model is carried out through the group discussion (FGD) method to increase the role of partners and GAPoktan members in managing natural resources. Then the ICB and TT models are implemented with the aim of improving the capabilities and quality of human resources by introducing the science and technology produced. The technology transferred to partners is an animal manure chopping machine or known as a chopper machine and an alternative animal feed chopping machine. Service activities were carried out on August 28 2023 and September 17 2023, where Gapoktan members were very enthusiastic about participating in each stage of the activity. The results of organic fertilizer processing increased by around 320%, while the resulting alternative animal feed can be stored for 2 to 3 weeks. Keywords  : chopper machine, organic fertilizer, gapoktan, increasing production.